Omphalocele containing an umbilical evagination of the bladder: A case report - D. Huijgen; H.P. Versteegh; J.M.J. Cornette; N.C.J. Peters; C.J.H.M. Meeussen; C.E.J. Sloots (Elsevier, 2023)
Background: An omphalocele is a common congenital abdominal wall defect, however co-occurring urological anomalies are rare. With the aim of optimizing treatment in future cases, we present a case of a male newborn with an omphalocele containing an unusual mucosal protruding mass, and give an overview of differential diagnosis and current literature. Case presentation: A newborn presented with an omphalocele containing small bowel, and a defect in the sac through which a protruding annular mucosal mass was visible. On previous prenatal ultrasounds, there were findings of an enlarged urinary bladder with patent urachus, communicating with a large allantoic cyst. The patient was taken to the operating room for exploration of the mucosal mass, which then appeared to be connected to an opening in the urinary bladder. The mucosal mass was successfully excised and the urinary bladder and abdominal wall defect were both primarily closed. Conclusions: Omphalocele with co-occurring urological anomalies are rare and come with a broad differential diagnosis. Surgeons must take prenatal, clinical and perioperative findings in consideration in order to adequately diagnose and treat the anomalies.